Pre-supernova activity as a possible explanation of the peculiar properties of Type IIP supernova 2009kf. Issue 2 (20th November 2020) - Ouchi, Ryoma; Maeda, Keiichi
ABSTRACT: SN 2009kf is an exceptionally bright Type IIP supernova (SN IIP) discovered by the Pan-STARRS 1 survey. The V -band magnitude in the plateau phase is MV  = −18.4 mag, which is much brighter than that for typical SNe IIP. We propose that its unusual properties can be naturally explained if we assume that there was a super-Eddington energy injection into the envelope in the last few years of the evolution before the SN explosion. Using a progenitor model with such a pre-SN energy injection, we can fit the observational data of SN 2009kf with a reasonable explosion energy of E exp  = 2.8 × 10 51 erg and 56 Ni mass of 0.25 M⊙ . Specifically, we injected the energy into the envelope at a constant rate of 3.0 × 10 39 erg s −1 in the last 3.0 yr of evolution before the core collapse. We propose that some unusually bright SNe IIP might result from pre-SN energy injection into the envelope.